Perceived dilemma between protective measures and social isolation in nursing homes during the COVID-19 pandemic: a mixed methods study among Swiss nursing home directors - Greindl, Stephanie; Di Gangi, Stefania; Plate, Andreas; Senn, Oliver; Neuner-Jehle, Stefan (Frontiers in Public Health, 2024)
Coronavirus pandemic particularly affected older adults, with the highest risks for nursing home residents. Governmental sStringent governmental protective measures for nursing homes unintendedly lead to social isolation of residents. Nursing home directors (NDs) found themselves in a dilemma between implementing protective measures and preventing the social isolation of nursing home residents.The objectives of this study were to describe protective measures implemented, to investigate NDs' perception of social isolation and its burden for nursing home residents due to these measures, and to explore experiences of NDs in the context of the dilemma.Cross-sectional embedded mixed-method study carried out by online survey between April 27 and June 09, 2022, among NDs in the German-speaking part of Switzerland.The survey consisted of 84 close-ended and nine open-ended questions. Quantitative findings were analyzed with descriptive statistics and qualitative data were evaluated using content analysis.The survey was completed by 398 NDs (62.8% female, mean age 55 [48-58] years) out of 1'044 NDs invited.3 NDs were highly aware of the dilemma. The measures perceived as the most troublesome were restrictions to leave rooms, wards or the home, restrictions for visitors, and reduced group activities. NDs and their teams developed a variety of strategies to cope with the dilemma, but were burdened themselves by the dilemma.As NDs were burdened themselves by the responsibility of how to deal best with the dilemma between protective measures and social isolation, supportive strategies for NDs are needed.